Oxygen Restriction Generates Difficult-to-Culture P. aeruginosa - Kvich, Lasse; Fritz, Blaine; Crone, Stephanie; Kragh, Kasper N.; Kolpen, Mette; Sønderholm, Majken; Andersson, Mikael; Koch, Anders; Jensen, Peter Ø.; Bjarnsholt, Thomas (Frontiers in Microbiology, 2019)
Induction of a non-culturable state has been demonstrated for many bacteria, e.g. E. coli and various Vibrio spp. In a clinical perspective, the lack of growth due to these non-culturable bacteria can have major consequences for the treatment of patients. Here we show how anoxic conditioning (restriction of molecular oxygen, O2) generates difficult-to-culture (DTC) bacteria during biofilm growth. A significant subpopulation of Pseudomonas aeruginosa entered a DTC state after anoxic conditioning, ranging from 5 to 90 % of the total culturable population, in both planktonic and biofilm models. Anoxic conditioning also generated DTC subpopulations of Staphylococcus aureus and Staphylococcus epidermidis (89 and 42 % of the total culturable population, respectively). Growth of the DTC populations were achieved by substituting O2 with 10 mM NO3- as an alternative electron acceptor for anaerobic respiration or, in the case of P. aeruginosa, by adding sodium pyruvate or catalase as scavengers against reactive oxygen species (ROS) during aerobic respiration. An increase in normoxic plating due to addition of catalase suggests the molecule hydrogen peroxide as a possible mechanism for induction of DTC P. aeruginosa. Anoxic conditioning also generated a true viable but non-culturable (VBNC) population of P. aeruginosa that was not resurrected by substituting O2 with NO3- during anaerobic respiration. These results demonstrate that habituation to an anoxic micro-environment could complicate diagnostic culturing of bacteria, especially in the case of chronic infections where oxygen is restricted due to the host immune response.